Improving the Conceptual Understanding Ability of Grade VIII Students Through the Guided Discovery Model Assisted by Interactive E-Modules - Dewantara, Ki Hajar; Dewi, Izwita (CV. Rayyan Dwi Bharata, 2025)
This research aims to: (1) To find out how the use of a guided discovery model assisted by interactive e-modules can increase students' understanding of concepts. (2) To determine the increase in students' understanding of concepts after using the guided discovery model assisted by interactive e-modules. The subjects of this research were all 33 students in class VIII-3. The first procedure of this research is to give an initial test to students, in order to see students' ability to understand initial concepts, the second is to carry out learning using a guided discovery model assisted by interactive e-modules with rectangular material. The research consisted of 2 cycles with a teaching process of 4 meetings, where after 2 meetings in each cycle a concept understanding test was given to see students' concept understanding abilities. The form of questions for each test is a description. Before the test is tested, it is first validated by a validator. In the initial test, students' conceptual understanding abilities were in the very poor category with an average of 29, where no students experienced the level of learning completeness. After the implementation of cycle I, the level of students' ability to understand concepts was in the poor category with an average of 57.93 and 5 students (15.15%) reached the level of learning completeness. In the implementation of cycle II, the level of students' ability to understand concepts was in the very good category with an average of 87.31 and 30 students (90.90%) reaching the criteria for completion. The G value on the gain index is 0.70035 in the high category, as well as the overall indicator criteria for understanding concepts and observations are in the good category (61-80%). Based on the research analysis, it is clear that the use of a guided discovery model assisted by interactive e-modules can improve the ability to understand concepts in class VIII students.